2017
DOI: 10.1007/s10637-017-0537-x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of reactive oxygen species to the anticancer activity of aminoalkanol derivatives of xanthone

Abstract: SummaryReactive oxygen species (ROS) are critically involved in the action of anticancer agents. In this study, we investigated the role of ROS in the anticancer mechanism of new aminoalkanol derivatives of xanthone. Most xanthones used in the study displayed significant pro-oxidant effects similar to those of gambogic acid, one of the most active anticancer xanthones. The pro-oxidant activity of our xanthones was shown both directly (by determination of ROS induction, effects on the levels of intracellular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Many investigations have found that the ROS levels in cancer cells are significantly associated with anticancer effect including proliferation inhibition and apoptosis induction. 30,[56][57][58][59] In order to explore the effect of Re-CDs on the inhibition of cancer cells, we measured the ROS level in A375 cells after they were treated with Re-CDs, by a flow cytometer. Results are displayed in Figure 6.…”
Section: Effect Of Re-cds On Ros Generation In Cancer Cellsmentioning
confidence: 99%
“…Many investigations have found that the ROS levels in cancer cells are significantly associated with anticancer effect including proliferation inhibition and apoptosis induction. 30,[56][57][58][59] In order to explore the effect of Re-CDs on the inhibition of cancer cells, we measured the ROS level in A375 cells after they were treated with Re-CDs, by a flow cytometer. Results are displayed in Figure 6.…”
Section: Effect Of Re-cds On Ros Generation In Cancer Cellsmentioning
confidence: 99%
“…It was reported that aminoalkanol-xanthones could generate the overexpression of manganese superoxide dismutase, thus decreasing reactive oxygen species (ROS)-mediated cell senescence. The aminoalkanol-xanthones also lead mitochondrial dysfunction and cellular apoptosis on the evaluated cancer cell lines [107]. The xanthone derivatives act as anticancer agents through several mechanisms of action.…”
Section: In Vitro Anticancer Assay Of Xanthone Derivativesmentioning
confidence: 97%
“…There are indications that generation of ROS plays a major role in the anticancer effect of biologically active compounds (Khan et al, 2021; Sypniewski et al, 2018). Furthermore, targeting the antioxidant defense mechanism of cancer cells and modulation of excessive ROS generation has also been identified as a therapeutic mechanism for inhibiting uncontrolled cell proliferation (Liu et al, 2014; Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%